W poszukiwaniu nowych (meta)modeli edukacji XXI wieku - Morbitzer, Janusz (Studia Edukacyjne, 2018)
The aim of the publication is to present new models of education appropriate to the twenty-first century and the needs of modern network society. The article presents a comprehensive substantiation for necessity changes in education, resulting from technological development, as well socio-cultural changes. The article characterizes selected models of education of the future: a new culture of learning, the school as a learning organization, so-called turquoise education, and education for wisdom and spirituality. It is emphasized that essential for the new models are new interpersonal relationships and basing on humanistic values rather than on new technologies.